Microstructure and mechanical properties of friction welded dissimilar AISI 1040 and AISI 304 steels - Balalan, Zulkuf; Yaz, Mehmet; Ekinci, Omer; Buldag, Sedat (Walter de Gruyter Gmbh, 2025)
The development of technology and the increase in needs have affected the manufacturing methods. It is of great importance to combine different materials to reduce costs and increase performance and design flexibility. Different parts can be joined by friction welding, which is a solid-state welding method. In this study, the weldability of AISI 304 stainless steel and AISI 1040 carbon steel with friction welding has been investigated. During welding, the temperature changes of the welds were measured. In addition to SEM, XRD, and EDS tests to examine the microstructure of the welds, tensile strength tests and hardness measurements were also performed to find out their mechanical characteristics. According to the analysis and test results, the best welding parameters were observed in the weld sample S6. As a result of this experimental study, it was seen that these different steels can be joined by friction welding.
Keywords: friction welding; AISI 304 steel; AISI 1040 steel; microstructure; mechanical properties